Management disclosure practices for disaggregated (financial) information in Slovenian unlisted companies - Daniel Zdolsek; Iztok Kolar (Journal for East European Management Studies, 2013)
The focus of the present study is the management practice of disclosing disaggregated (financial) information in a company's annual report. In this study, a sample of 232 Slovenian unlisted companies has been examined. The results show that less than a quarter of the companies disclose disaggregated information. Moreover, the multiple regression analysis reveals that the scope of the disclosed disaggregated information is not influenced by the company's size, financial leverage, profitability or growth, but that only a company's membership in the construction industry sector is a relevant determinant. Furthermore, additional analysis reveals that the companies' proprietary information does not influence the management practices regarding which disaggregated information to disclose. – – Die vorliegende Studie befasst sich mit Berichterstattungspraktiken des Managements in Bezug auf segmentierte (Finanz-)Daten im Jahresbericht slowenischer Unternehmen. In dieser Studie wurde eine Auswahl von 232 slowenischen nicht börsennotierten Unternehmen untersucht. Die Ergebnisse zeigen, dass segmentierte Informationen von weniger als einem Viertel der Unternehmen offengelegt werden. Darüber hinaus zeigt die multiple Regressionsanalyse, dass der Umfang der offengelegten segmentierten Daten nicht etwa durch die Unternehmensgröße, dem Verhältnis von Fremdkapital zu Eigenkapital ('Financial Leverage'), Rentabilität oder Wachstum des Unternehmens beeinflusst wird. Relevant ist die Tatsache, ob die Unternehmen in der Baubranche tätig sind. Darüber hinaus beeinflussen firmeneigene (proprietäre) Informationen die Berichterstattungspraktiken des Managements, insbesondere in Bezug auf die Auswahl der offenzulegenden segmentierten Daten, nicht.
Keywords: 650; studies; disaggregated (financial) information disclosures; management's choice of disclosure policy; management behavior; strategic management; Slovenia; Segmentberichterstattung; Jahresabschluss; Bauwirtschaft; Slowenien